Pembuatan Biopori Sebagai Upaya Pengelolaan Sampah Organik di Dusun Santren - Hestiana Kusumaningsih; Herlin Nurlitasari; Annisa Putri Utami; Adib Suyanto (JGEN : Jurnal Pengabdian Kepada Masyarakat, 2024)
This Community Service Program activity is located in Santren Hamlet, Soronalan Village, Sawangan District, Magelang Regency. Santren is a hamlet located on the slopes of Mount Merbabu. This hamlet is still beautiful and its nature is still preserved. However, there are still many people who ignore the environment and their health. It has been proven that organic waste is not being utilized, which is simply thrown onto the mountain slopes. Therefore, the Ministry of Health Yogyakarta Health Polytechnic chose a location in Santren Hamlet and applied the knowledge gained in lectures to be transmitted to the Santren Hamlet. The work program implemented is also in accordance with the major taken, namely biopore as organic waste processing. Biopores are vertical cylindrical holes in the soil as a method of utilizing organic waste and water absorption. The aim of this socialization is so that the residents of Santren Hamlet are able to process organic waste. The result of this activity was the installation of 6 biopore absorption holes in Santren Hamlet.